Caution, this is Sparta!: a gendered examination of mixed martial arts and the spartanization process - Teeter, Allison M. (Kansas State University, 2014)
The sport of Mixed Martial Arts (MMA) was once referred to as a No Holds Barred (NHB) fighting contest, but is now known as cage, extreme, or ultimate fighting. Showcasing athletes from a variety of martial arts backgrounds, a referee stoppage, knockout, or submission is the only way to win. Pushing their minds and bodies to the limits, fighters often engage in hand-to-hand combat inside of a ring or cage in front of a crowd, for anywhere from three to twenty-five minutes. How does one become an MMA fighter? Through a rigorous and complex process of socialization that will be referred to in this work as the ‘spartanization’ process. A mixed methodological approach, primarily qualitative in nature, was used to reveal the rigorous and complex nature of this process. This study’s data collection began with six site visits taking place over the course of six months. Utilizing a convenience sampling method, in-depth semi-structured interviews were conducted with 31 male and 14 female fighters. The interview schedule addressed fighters’ involvement in the spartanization process, their experiences in the gym as well as the cage, and their perceptions as fighters. Male and female participants described the spartanization process and ascribed meaning to it in similar ways. Their motivations for becoming MMA fighters are explained using theories of identity and alienation. Findings demonstrate that the sport of MMA and process of becoming a fighter are both highly gendered. One was neither found to be more nor less gendered than the other, but according to this study’s findings women are more likely to feel the effects of gender at the organizational level than they are a the level of training. Not sure what MMA is? Never heard of the UFC before? Do not worry, the histories of both are provided. By reading this work you will also learn more about the athletes participating in this sport, and discover whether or not you have what it takes to be the next ‘ultimate fighter.’
Keywords: Sociology; Gender; Mixed Martial Arts (MMA); Sports; Spartanization; Gender Studies (0733); Sociology (0626)